Effects of Nano-zero-valent Iron and Earthworms on Soil Physicochemical Properties and Microecology in Cadmium-Contaminated Soils - Bincheng Tang; Yufen Zi; Chang’e Liu; Minhui Yue; Yue Zhang; Weilan Zhang; Jinquan Chen; Changqun Duan (Water, Air, & Soil Pollution, 2024)
The capacity of nano-zero-valent iron (nZVI) and soil animals to remediate heavy metal–contaminated soil has been widely studied. However, the synergistic effect of soil animals and nZVI has not been thoroughly investigated. Here, we studied the combined effect of earthworms and nZVI on soil physicochemical properties and microecology during remediation of cadmium (Cd)–contaminated soil. The results showed that although amendment with nZVI reduced earthworm survival and biomass, the combination of nZVI and earthworms was effective at reducing the available Cd (ACd) content of soil and improving its quality. ACd most effectively reduced by 75.3% in the presence of earthworms under the 0.25% nZVI combination. Meanwhile, the combined action of earthworms and nZVI significantly improved soil properties and increased the diversity of soil microorganisms. In the earthworm-free system, nZVI reduced ACd by increasing soil pH and the abundance of Stenotrophobacter in Cd-contaminated soil, in addition to the co-precipitation and adsorption reported in previous studies. Correlation analysis revealed that the combination of nZVI and earthworms synergistically decreased ACd by decreasing soil OM and increasing the relative abundance of Opitutus and Gemmatta . Overall, our study indicates that the combination of nano-zero-valent iron and earthworms is a potential system for in situ remediation of Cd-contaminated soils and provides a deep understanding of the mechanisms involved in remediation.